Analysis of the risk factors for severe lung injury after radical surgery for tetralogy of fallot - He, Yan; Zhang, Hong-Sheng; Zhang, Ting-Zhou; Feng, Yu; Zhu, Yan; Fan, Xing (Frontiers in Surgery, 2022)
Objective: To determine the risk factors for severe lung injury (SLI) (PaO2/FiO2 <150) after radical surgery for tetralogy of Fallot with pulmonary stenosis (TOF/PS)in children. Methods: A retrospective analysis was conducted on a total of 287 children with TOF/PS aged less than 10 years (including 166 boys) who received radical surgery at the Center of Pediatric Heart Disease of the Beijing Anzhen Hospital from 2018 to 2020. Results: A total of 83 cases (28.9%) had SLI after surgery. Univariate analysis showed that age, weight, pulmonary artery index (PAI), cardiopulmonary bypass (CPB) time, and polymorphonuclear leukocyte (PMN) percentage on the first day after surgery were risk factors for SLI after surgery. Multivariate logistic regression analysis showed that PAI, PMN percentage on the first day after surgery, and CPB time were independent risk factors for SLI after surgery. The prediction model was established: Logit(P) =2.236+0.009*CPB-0.008*PAI-0.035*PMN, AUC=0.683, P<0.001, sensitivity 65.8%, specificity 68.6%. After surgery, static lung compliance was significantly lower in the SLI group than in the routine group. Complication rates, and mortality were significantly higher in the SLI group than in the routine group. Ventilator support times, length of ICU stays, and total lengths of hospital stay were significantly longer in the SLI group than in the routine group. Conclusion: SLI following radical surgery for TOF in children significantly affects postoperative recovery, and PAI, PMN percentage on the first day after surgery, and CPB time are independent risk factors for SLI.